A mid- and long-term follow-up study on the bilateral pedicle anchoring technique with percutaneous vertebroplasty for the treatment of Kümmell's disease - Dai, Shichang; Du, Yu; Chen, Liang; Xu, Yifan; Hu, Qiong (Frontiers in Surgery, 2023)
Study design Retrospective study of clinical and radiological parameters. Objective To investigate the clinical efficacy and long-term stability of bone cement of the bilateral pedicle anchoring technique with percutaneous vertebroplasty (PVP) in the treatment of Kümmell's disease (KD). Summary of background data The optimal treatment regimen for KD remains controversial. With the development of minimally invasive orthopedic techniques, PVP has been widely recognized for its advantages, such as less surgical trauma, shorter operation time, less blood loss, quick recovery, and pain relief. Previous reports indicate that in patients who undergo PVP for KD, bone cement may be displaced, causing pain recurrence, or it may enter the spinal canal and cause spinal cord compression, especially in the long term. Theoretically, the bilateral pedicle anchoring technique can enhance the stability of the bone cement in the vertebral body and reduce the occurrence of long-term bone cement displacement. However, there are few reports on the use of this technique to treat KD. This study reports the mid- and long-term follow-up of the clinical and radiological outcomes of the bilateral pedicle anchoring technique with PVP for the treatment of KD. Methods From January 2016 to January 2019, 41 patients with KD treated using the bilateral pedicle anchoring technique with PVP in our hospital were enrolled. There were 10 men and 31 women with an average age of 76.5 ± 8.0 years (range: 55–92 years). The average follow-up duration was 19.3 ± 8.0 months (range: 12–38 months). Visual analog scale (VAS) scores, Oswestry disability index (ODI), anterior vertebral height, kyphotic angle, and wedge angle were recorded before surgery, 1 day after surgery, and at the last follow-up. Clinical efficacy, vertebral height recovery, and bone cement displacement were analyzed in combination using plain radiographs, computed tomography, magnetic resonance imaging, and other imaging data. Results All the patients successfully underwent the procedure without serious complications. No obvious displacement of bone cement was found in the imaging data obtained 1 day after the operation and at the last follow-up. VAS scores, ODI scores, anterior vertebral height, kyphotic angle, and wedge angle of the injured vertebrae significantly improved after surgery. There was no significant difference between the anterior vertebral height, kyphotic angle, and wedge angle of the vertebral body obtained 1 day after surgery and those obtained at the last follow-up. Bone cement leakage occurred in seven patients, with no abnormal clinical symptoms. Conclusion The bilateral pedicle anchoring technique with PVP integrates the use of bone cement in both the vertebral body and the bone cement in the pedicle, enhances the stability of the bone cement, and effectively prevents the displacement of the intravertebral bone cement. The postoperative bone cement stability was high, the clinical effect was obvious, and the long-term follow-up results were satisfactory. Hence, this is a safe and effective surgical method for the treatment of KD.